Transient mathematical prediction and experimental verification of the charging characteristics of subsea accumulators. (August 2022) - Li, Wang; Liu, Qingyou; Tang, Yang
This study is focused on the charging characteristics of the subsea accumulators used to provide power for safety on a subsea well. The charging time and storage volume are strictly limited according to API specification for a subsea accumulator system. Long hydraulic lines must be used to cope with the depth of seawater, which will significantly increase the charging time and cause a large pressure drop. In addition, the pressure in hydraulic pump and subsea accumulators used also varies with charging. A transient flow will occur during the charging of the system. In this paper, a systematic transient mathematical model (STMM) of the subsea accumulator charge system is established. The STMM includes three main parts: the air driven liquid pump, the long hydraulic pipeline, and the subsea accumulator. A double-coefficient unsteady friction model based on instantaneous acceleration is applied in the long pipeline model. The Redlich–Kwong real gas state equation is used to calculate the gas in the accumulator. A series of charging experiments for two rated working pressure of 10, 000 psi and 15, 000 psi on the ground were carried out. The results of the experiment showed very consistently with those of the STMM. The liquid pressure in the accumulator is divided into three stages during charging: rapidly increasing stage, slowly increasing stage, and maintaining constant stage. Moreover, an engineering proposal was presented to reduce the design pressure requirements of the system. Furthermore, the charging time will increase significantly as the length of the pipe increases, but decreases as the inner diameter of the pipe increases. The paper outlines a direction for the design theory and engineering practice of the subsea accumulator charge system.